РОЛЬ ПОРЯДКА СЛОВ И АКТУАЛЬНОГО ЧЛЕНЕНИЯ В СОЗДАНИИ ТЕКСТА - Исрафилова, Г. Ф. (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the role of word order and actual membership in the formation of a text. Generally these two categories are very important in text formation. As states O. Moscolskaya the word order helps to build up combinations between sentences to combine the components from grammatical point of view, as well as to emphasize the meaning of the sentence. A. Mamedov states about it: The analize of the event word order demands the address to larger frame than sentence frame. It does not depend on which genre the text is, but the word order differs from one text to another. It means that the word order in scientific texts is completely differs from the word order in literary texts. Sometimes the actual membership is understood as the meaning membership. In order to express some opinion clearly the sentences joined in connected way and form the text. Y. Lotman writes about actual membership: "The actual membership of sentence reflects the functional perspectives of the sentence, in other words the manner of joining of the sentence in the act of communication.